Insulating adhesive, black light-absorbing composition and battery monomer
By using light-transmitting insulating glue, the problem of burrs arises when laser cutting the electrode sheet is solved, and the effect of improving cutting efficiency and cell safety is achieved.
Patent Information
- Application Number
- CN202210378590.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-04-08
AI Technical Summary
During the battery production process, burrs are easily generated when laser cutting the electrode sheet, which affects cutting efficiency and battery cell safety. The existing methods of removing burrs can only hide burrs and cannot be fundamentally reduced or eliminated.
A light-transmissible insulating glue is provided, containing polyvinylidene fluoride (PVDF), quartz sand and N-methylpyrrolidone (NMP). The insulating glue absorbs less laser energy, allowing the laser to transmit through the irradiation current collector, thereby directly fusing the current collector, and softening and disconnecting the insulating glue through heat transfer to avoid burrs.
It effectively avoids the burr caused by excessive heat absorption of the current collector during the cutting process, improves the cutting rate and efficiency, and enhances the safety of the battery cell.
Smart Images

Figure CN116925604B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to an insulating adhesive and a black light-absorbing composition that can be used in combination with the insulating adhesive; in addition, the present application also relates to a battery cell, a battery including the battery cell, and an electrical device. Background Art
[0002] In the battery production process, when cutting the battery pole piece, a layer of insulating glue is usually applied to the edge of the active material on the pole piece to enhance the safety of the battery cell. However, when using laser to cut the pole piece coated with insulating glue, burrs are easily generated, which also affects the cutting efficiency.
[0003] The current method of removing burrs is to do it after the burrs are generated. After the burrs are generated, a rolling machine is used to roll the edge of the pole piece, thereby pressing the burrs into the film layer. However, this method can make the burrs not exceed the thickness direction of the pole piece and hide the burrs, but it cannot fundamentally reduce or even eliminate the burrs. During the battery cycle, these burrs may come out again due to external or internal forces, thus affecting the safety of the battery cell.
[0004] Therefore, there is still a need for a method to fundamentally reduce or even eliminate burrs. Summary of the invention
[0005] The present application provides a method to fundamentally reduce or even eliminate the generation of burrs.
[0006] A first aspect of the present application provides an insulating adhesive comprising polyvinylidene fluoride (PVDF for short), quartz sand and N-methylpyrrolidone (NMP for short).
[0007] In the process of laser cutting the pole piece to form the pole ear, if the current collector absorbs too much heat, burrs will be easily formed, thus affecting the safety of the battery cell. The insulating glue used in the prior art is basically opaque. When cutting the current collector coated with the insulating glue by laser or other energy beams, the laser is first irradiated on the insulating glue. Since the insulating glue is opaque, the laser is basically absorbed by the insulating glue first. In the process of cutting the insulating glue, energy is continuously accumulated on the current collector. When the laser cuts the current collector, the current collector has accumulated too much energy, so burrs are easily formed during the cutting process. In contrast, the insulating glue provided in the present application is translucent and absorbs less laser energy. Therefore, the laser can pass through the insulating glue and irradiate on the current collector (such as aluminum foil), so that the current collector directly absorbs the laser energy and starts to melt first. In addition, while absorbing heat, the current collector will transfer heat to the insulating glue, causing the insulating glue to absorb a small amount of energy brought by the laser while also absorbing the heat transferred by the current collector, thereby softening and disconnecting. In this way, it is helpful to avoid the current collector absorbing too much energy and generating burrs. In addition, since the current collector directly absorbs most of the laser energy, the cutting speed of the current collector can be increased, and the cutting efficiency can be accelerated. The current collector can be cut first and then the insulating glue can be cut, or the current collector and the insulating glue can be cut at the same time.
[0008] In the insulating adhesive described in the present application, PVDF mainly plays the role of insulation and dispersion of quartz sand. The quartz sand plays the role of increasing the brittleness of the insulating adhesive so that the adhesiveness of the insulating adhesive is not too large, and does not affect the light transmittance of the insulating adhesive. NMP exists as a solvent.
[0009] In any embodiment, the weight content of the PVDF is in the range of 3-7%, the weight content of the quartz sand is in the range of 13-23%, and the weight content of the N-methylpyrrolidone (NMP for short) is in the range of 75-84%, based on the total weight of the insulating glue.
[0010] The weight contents of PVDF, quartz sand and NMP within the above ranges can ensure that the insulating adhesive has suitable properties for coating and laser cutting of current collectors.
[0011] In any embodiment, the viscosity of the insulating adhesive is in the range of 500 to 2000 mPa·s.
[0012] The insulating adhesive viscosity within the above range can ensure the consistency of the insulating adhesive coating thickness, and can ensure that the insulating adhesive coating thickness of 10μm to 60μm can be achieved, meeting the requirements of battery cell design. If the insulating adhesive viscosity is too high, the requirement of the thickest thickness being less than 60μm cannot be met; if it is too low, the requirement of the thinnest thickness being greater than 10μm cannot be met.
[0013] In any embodiment, advantageously, the transparency of the insulating adhesive is ≥ 97%. The higher the transparency, the better, and high transparency can ensure the efficiency of laser penetrating the insulating adhesive. If the transparency is too low, it may affect the speed of laser cutting.
[0014] In any embodiment, advantageously, the tear strength of the insulating adhesive is in the range of 5 to 12 kN / m. The smaller the tear strength of the insulating adhesive, the better. The tear strength within the above range can ensure a suitable cutting speed. If the tear strength is too large, the cutting speed may be reduced.
[0015] In any embodiment, advantageously, the average particle size of the quartz sand used to prepare the insulating adhesive is in the range of 5 to 30 μm. The average particle size in the above range can ensure the appropriate viscosity range of the insulating adhesive and the manufacturing efficiency of the insulating adhesive.
[0016] In any embodiment, advantageously, the weight average molecular weight of the PVDF is in the range of 600,000 to 700,000. The weight average molecular weight of the PVDF in the above range can ensure the appropriate viscosity range of the insulating adhesive and the manufacturing efficiency of the insulating adhesive. If the molecular weight is too large or too small, the viscosity of the insulating adhesive may be inappropriate.
[0017] The second aspect of the present application provides a black light-absorbing composition, which includes polyvinylidene fluoride, carbon black and N-methylpyrrolidone. Optionally, the weight content of the polyvinylidene fluoride is in the range of 1 to 3%, the weight content of the carbon black is in the range of 5 to 35%, and the weight content of the N-methylpyrrolidone is in the range of 70 to 90%, based on the total weight of the black light-absorbing composition.
[0018] In the black light-absorbing composition, PVDF plays a role in dispersing carbon black, and carbon black mainly plays a role in absorbing light. The weight contents of polyvinylidene fluoride, carbon black and N-methylpyrrolidone are within the above ranges, which can ensure that the black light-absorbing composition has a suitable viscosity range and a suitable absorbance.
[0019] In any embodiment, advantageously, the viscosity of the black light absorbing composition is in the range of 100 to 500 mPa·s. The viscosity of the black light absorbing composition in the range can ensure a suitable coating thickness of the black light absorbing composition. If the viscosity is too high, the coating thickness may be too thin, and if the viscosity is too low, the coating thickness may be too thick.
[0020] In any embodiment, advantageously, the absorbance of the black light absorbing composition is ≥ 98.0%, optionally ≥ 99.9%.
[0021] The greater the absorbance of the black light-absorbing composition, the better. The greater the absorbance, the more laser energy can be absorbed and transferred to the current collector, which is helpful for cutting the current collector. If the value is too small, it may affect the speed of laser cutting the pole piece.
[0022] In any embodiment, the weight average molecular weight of the PVDF in the black light absorbing composition is in the range of 500,000 to 700,000. The weight average molecular weight of the PVDF in the black light absorbing composition is within the range, which can ensure that the black light absorbing composition has a suitable viscosity range and ensure the manufacturing efficiency of the black light absorbing composition. If the molecular weight is too large or too small, the viscosity range of the black light absorbing composition may be inappropriate and the manufacturing efficiency may be low.
[0023] In any embodiment, the average particle size of the carbon black used to prepare the black light absorbing composition is 0.1 to 1 μm.
[0024] A third aspect of the present application provides a battery cell, comprising:
[0025] An electrode assembly, the electrode assembly comprising a main body and a current collector extending from at least one end of the main body;
[0026] The insulating glue described in the present application and / or the black light-absorbing composition described in the present application, wherein the insulating glue and / or the black light-absorbing composition covers at least a portion of the current collector; and
[0027] A shell in which the electrode assembly is accommodated.
[0028] The insulating glue described in the present application is at least located in the area of the current collector (i.e., the current collector extending from at least one end of the main body) close to the active material area, and has the following advantages: on the one hand, it is convenient to control the laser when die-cutting the current collector to avoid excessive energy affecting other areas; on the other hand, it can enhance the strength of the root of the current collector and play a role in insulation protection, avoiding the current collector or the pole ears formed after die-cutting or possible burrs from being inserted into the active material area or the main body, causing a short circuit.
[0029] A fourth aspect of the present application provides a battery, which includes the above-mentioned battery cell.
[0030] A fifth aspect of the present application provides an electrical device, which includes the above-mentioned battery, and the battery is used to provide electrical energy.
[0031] The sixth aspect of the present application provides a method for cutting a current collector using laser, which includes using the above-mentioned insulating glue and / or the above-mentioned black light-absorbing composition.
[0032] As described above, the insulating adhesive described in the present application is used in the process of cutting the pole piece, which can improve the cutting rate and efficiency and avoid or reduce the generation of burrs during the cutting process. The black light-absorbing composition described in the present application can reduce the reflection of the aluminum foil to the laser and improve the absorption of the laser energy and transfer it to the current collector, thereby facilitating the cutting of the current collector. In the process of cutting the pole piece, the insulating adhesive described in the present application and the black light-absorbing composition described in the present application are used simultaneously, which can greatly improve the cutting speed while avoiding the generation of burrs and save laser energy.
[0033] In any embodiment, in the method of cutting the current collector using laser, the insulating glue described in the present application and the black light-absorbing composition described in the present application are used simultaneously, and the black light-absorbing composition is first coated on the current collector, and then the insulating glue is coated on the current collector coated with the black light-absorbing composition.
[0034] The use of the light-transmissive insulating adhesive and the black light-absorbing composition described in the present application can concentrate the laser energy on the cutting part of the pole piece to be cut to a large extent, significantly improving the cutting efficiency. In addition, the black light-absorbing composition described in the present application is applied to the pole piece, which can quickly absorb the laser energy and transfer most of the energy to the current collector, thereby accelerating the cutting of the current collector. Therefore, the black light-absorbing composition described in the present application is usually applied to the current collector to be cut before applying the insulating adhesive.
[0035] In any embodiment, in the method of cutting the current collector using laser, the black light-absorbing composition is coated on the cutting position on the current collector by gravure coating; optionally, the insulating glue is coated on the current collector to be cut by extrusion coating.
[0036] For the coating of the black light-absorbing composition, gravure coating can meet the requirement of 1 to 3 μm thickness of the black light-absorbing coating. It should be understood that any other coating method is also feasible, as long as it can achieve smooth coating of the black light-absorbing composition with appropriate thickness. For the coating of the insulating adhesive, extrusion coating can accurately control the coating thickness of the insulating adhesive. It should be understood that any other coating method is also feasible, as long as it can achieve smooth coating of the insulating adhesive with appropriate thickness.
[0037] The black light-absorbing composition described in the present application is coated on the current collector of the pole piece, which can quickly absorb laser energy and transfer most of the energy to the current collector, thereby accelerating the cutting of the current collector. Therefore, the black light-absorbing composition described in the present application is usually coated on the cutting position of the pole piece irradiated by the laser. The coating of the insulating glue described in the present application can improve the safety of the battery cell on the one hand, and improve the efficiency of pole piece cutting while avoiding or reducing the generation of burrs on the other hand. Therefore, it is usually coated on the edge of the active material on the pole piece, and also on the current collector that is not in contact with the active material. For a specific implementation method, see Figure 1 .
[0038] In any embodiment, in the method of cutting the current collector using laser, the insulating glue described in the present application is used, and the coating thickness of the insulating glue is in the range of 10 to 60 μm, and the optional range is 30 to 40 μm; optionally, the coating width is 2 to 5 mm, and the optional range is 3 to 4 mm.
[0039] The insulating glue coating thickness range described in the present application is within the above range, which can provide sufficient insulation performance, and at the same time can reduce or avoid the risk of short circuit caused by burrs formed during laser cutting of the positive electrode sheet piercing through the diaphragm and contacting the negative electrode or burrs formed during laser cutting of the negative electrode sheet piercing through the diaphragm and contacting the positive electrode.
[0040] In any embodiment, in the method of cutting the current collector using laser, the black light-absorbing composition described in the present application is used, and the coating thickness of the black light-absorbing composition is 1 to 5 μm, and can be 1 to 3 μm, and the coating width is 0.5 to 2 mm, and can be 0.5 to 1 mm.
[0041] The coating thickness and coating width of the black light-absorbing composition are within the above range, which can avoid burrs during laser cutting and increase the cutting speed. It can also reduce or avoid the risk of short circuit caused by burrs formed during laser cutting of the positive electrode sheet piercing through the diaphragm and contacting the negative electrode, or by burrs formed during laser cutting of the negative electrode sheet piercing through the diaphragm and contacting the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figures 1 to 7 In the figure, the same graphic area represents the same thing. The area with a slash represents the substrate of the electrode, that is, the current collector; the gray patternless area represents the membrane area, that is, the active material area, located on both sides of the current collector; the white area with black dots represents the insulating glue; the black area inside the insulating glue is the black light-absorbing formula, that is, the black light-absorbing composition, and the vertical triangle composed of horizontal short lines is the cutting laser, that is, the laser used for cutting.
[0043] Figure 1This is a schematic cross-sectional view of a pole piece coated with a black light-absorbing composition and an insulating adhesive before laser cutting of the pole piece (actually the current collector is cut) in one embodiment of the present application. In this figure, the active material is coated on both sides of the current collector, the insulating adhesive is coated on the area of the pole piece that is not coated with the active material and is in direct contact with the active material at the edge of the active material, and the black light-absorbing composition is coated on the area of the pole piece that is not coated with the active material and is covered by the insulating adhesive. In terms of operation, the black light-absorbing composition is first applied to the part of the current collector that needs to be cut, and then the insulating adhesive is applied.
[0044] Figure 2 for Figure 1 Schematic diagram of top view of the pole piece in FIG. In this figure, a long strip of black light-absorbing composition is coated on the current collector.
[0045] Figure 3-5 This is a schematic diagram of using laser to cut pole pieces in one embodiment of the present application.
[0046] Figure 3 A schematic diagram showing that laser light enters from above a pole piece coated with a black light-absorbing composition and an insulating adhesive, passes through the insulating adhesive, and irradiates the coating of the black light-absorbing composition.
[0047] Figure 4 Schematic diagram showing that the current collector (substrate) melts first after absorbing enough heat.
[0048] Figure 5 A schematic diagram showing that after the current collector (substrate) is melted, the insulating adhesive is disconnected after absorbing the laser energy and the residual heat at the current collector (substrate).
[0049] Figure 6 Schematic diagram of a top view of a laser cutting pole piece. In the figure, the dotted line is the laser cutting path. Ideally, the black light absorbing composition can be applied accurately along the cutting path. The figure shows a schematic diagram of applying the black light absorbing composition only along a straight line.
[0050] Figure 7 This is a schematic diagram of a burr formed during laser cutting of a positive electrode sheet piercing through the separator and contacting the negative electrode, thereby forming a short circuit. The slashed triangular area in contact with the negative electrode in the figure is the burr formed during laser cutting of the positive electrode sheet. After adopting the insulating glue of the present application, the occurrence of this situation can be avoided or reduced.
[0051] Figure 1-7 This is a schematic diagram. The dimensions and relative sizes of the components shown in the figure do not represent the actual dimensions and actual relative sizes. DETAILED DESCRIPTION
[0052] Hereinafter, the embodiments of the insulating glue and the black light-absorbing composition of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0053] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those generally understood by technicians in the technical field of this application; the terms used in the specification of this application are only for the purpose of describing specific implementation methods and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. If not otherwise specified, the "including" and "comprising" mentioned in this application represent open-ended or closed-ended. For example, the "including" and "comprising" may mean that other components not listed may also be included or contained, or may only include or contain listed components.
[0054] The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order or a primary and secondary relationship.
[0055] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-6. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0058] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0059] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", and "attached" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0060] The term "and / or" in this application is merely a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this application generally indicates that the previously associated objects are in an "or" relationship. Unless otherwise specified, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0061] In the embodiments of the present application, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0062] It should be understood that the thickness, length, width and other dimensions of various components in the embodiments of the present application shown in the drawings, as well as the overall thickness, length, width and other dimensions of the integrated device are only exemplary and should not constitute any limitation to the present application.
[0063] The term "plurality" used in the present application refers to two or more (including two).
[0064] In this application, "laser cutting of pole pieces" means using laser to cut the current collector in the pole piece. It should be understood that the insulating glue and black light-absorbing composition described in this application are suitable for use in processes using laser or other energy beams to cut metals, and are not limited to the pole pieces or current collectors described in this application.
[0065] In the current battery production process, when laser is used to cut the pole piece, in order to protect the battery cell, a layer of insulating glue is coated on the edge of the active material on the pole piece. However, when laser cutting is used, the laser is first irradiated on the insulating glue. Since the insulating glue is opaque, the insulating glue is cut first, and then the current collector (such as aluminum foil) is cut. This makes it easy for the current collector to absorb too much heat, causing the current collector to melt and then produce burrs. Unexpectedly, the present application provides a special insulating glue. By using this insulating glue, when laser is used to cut the pole piece, the laser can be irradiated on the current collector through the insulating glue, so that the current collector can be cut first or cut at the same time as the insulating glue, and then the insulating glue is cut, thereby well solving the above-mentioned problem and improving the cutting efficiency.
[0066] Therefore, a first aspect of the present application provides an insulating adhesive comprising polyvinylidene fluoride, quartz sand and N-methylpyrrolidone.
[0067] During the process of laser cutting the pole piece to form the pole ear, if the current collector absorbs too much heat, burrs will easily form, thus affecting the safety of the battery cell. The insulating glue used in the prior art is basically opaque. When a laser or other energy beam is used to cut the current collector coated with the insulating glue, the laser is first irradiated on the insulating glue. Since the insulating glue is opaque, the laser is first absorbed by the insulating glue. During the process of cutting the insulating glue, energy is continuously accumulated on the current collector. By the time the laser cuts the current collector, the current collector has accumulated too much energy, so burrs are easily formed during the cutting process. In contrast, the insulating glue provided in the present application is light-transmissive and absorbs less laser energy. Therefore, the laser can pass through the insulating glue and irradiate on the current collector (such as aluminum foil) (see Figure 3 ), whereby the current collector directly absorbs the laser energy and starts to fuse first (see Figure 4 In addition, the current collector transfers heat to the insulating glue while absorbing heat, so that the insulating glue absorbs a small amount of energy from the laser while also absorbing the heat transferred from the current collector, thereby softening and disconnecting (see Figure 5). This helps to avoid the current collector absorbing too much energy and generating burrs. In addition, since the current collector basically directly absorbs most of the laser energy, the cutting speed of the current collector can be increased and the cutting efficiency can be accelerated. The use of the insulating glue described in the present application to cut the current collector can make the current collector be cut first and then the insulating glue, or the current collector and the insulating glue can be cut at the same time. It should be understood that the present application also covers the situation where the insulating glue may be cut first and the current collector begins to be cut during the cutting process.
[0068] In the insulating adhesive described in the present application, PVDF mainly plays the role of insulation and dispersion of quartz sand. The quartz sand plays the role of increasing the brittleness of the insulating adhesive so that the insulating adhesive will not stick together, and does not affect the light transmittance of the insulating adhesive. NMP exists as a solvent.
[0069] It should be understood that the insulating adhesive may include substances other than PVDF, NMP and quartz sand. Optionally, the insulating adhesive only includes PVDF, NMP and quartz sand.
[0070] In some embodiments, the PVDF weight content ranges from 3 to 7%, the quartz sand weight content ranges from 13 to 23%, and the N-methylpyrrolidone (NMP for short) weight content ranges from 75 to 84%, based on the total weight of the insulating adhesive.
[0071] Optionally, the weight content of the polyvinylidene fluoride may be approximately 4.25%±1%, the weight content of the quartz sand may be approximately 17%±1%, and the weight content of the N-methylpyrrolidone (NMP for short) may be approximately 78.72%±1%.
[0072] The weight content of PVDF, quartz sand, and NMP within the above range can ensure that the insulating adhesive has suitable properties for coating and laser cutting of the current collector. It should be understood that the weight content is variable and may have different optimal ranges in different application scenarios. The range of the above substances disclosed in the present application can achieve better results when cutting the current collector.
[0073] It should be understood that although the present application discloses a combination of PVDF, quartz sand and NMP, the concept of the present application is not limited thereto. Any substance that can play the same role as PVDF can replace the PVDF or be used together with the PVDF in the insulating adhesive. Similarly, any substance that can play the same role as quartz sand can replace the quartz sand or be used together with the quartz sand in the insulating adhesive, and any substance that can play the same role as NMP can replace NMP or be used together with NMP in the insulating adhesive.
[0074] In some embodiments, the viscosity of the insulating adhesive ranges from 500 to 2000 mPa·s, and can be optionally 500 to 1000 mPa·s.
[0075] The insulating adhesive viscosity within the above range can ensure the consistency of the insulating adhesive coating thickness, and can ensure that the insulating adhesive coating thickness of 10μm to 60μm can be achieved, meeting the requirements of battery cell design. If the insulating adhesive viscosity is too high, the requirement of the thickest thickness being less than 60μm cannot be met; if it is too low, the requirement of the thinnest thickness being greater than 10μm cannot be met.
[0076] In some embodiments, advantageously, the transparency of the insulating adhesive is ≥ 97%. The higher the transparency of the insulating adhesive described in the present application, the better. High transparency can ensure the efficiency of laser penetrating the insulating adhesive. If the transparency is too low, it may affect the speed of laser cutting.
[0077] In some embodiments, advantageously, the tear strength of the insulating adhesive is in the range of 5 to 12 kN / m. The smaller the tear strength of the insulating adhesive, the better. The tear strength within the above range can ensure a suitable cutting speed. If the tear strength is too large, the cutting speed may be reduced.
[0078] In some embodiments, advantageously, the average particle size of the quartz sand used to prepare the insulating adhesive is in the range of 5 to 30 μm. The average particle size of the quartz sand in the above range can ensure the appropriate viscosity range of the insulating adhesive and the manufacturing efficiency of the insulating adhesive.
[0079] The quartz sand described in the present application may be quartz sand with the highest possible transparency, such as at least translucent quartz sand, preferably fully transparent quartz sand.
[0080] In some embodiments, advantageously, the weight average molecular weight of the PVDF is in the range of 600,000 to 700,000. The weight average molecular weight of the PVDF in the above range can ensure the appropriate viscosity range of the insulating adhesive and the manufacturing efficiency of the insulating adhesive. If the molecular weight is too large or too small, the viscosity of the insulating adhesive may be inappropriate.
[0081] The second aspect of the present application provides a black light-absorbing composition, which includes polyvinylidene fluoride, carbon black and N-methylpyrrolidone. Optionally, the weight content of the polyvinylidene fluoride is in the range of 1 to 3%, the weight content of the carbon black is in the range of 5 to 35%, and the weight content of the N-methylpyrrolidone is in the range of 70 to 90%, based on the total weight of the black light-absorbing composition.
[0082] Optionally, the weight content of the polyvinylidene fluoride may be in the range of 2.65%±1%, the weight content of the carbon black may be in the range of 12.5%±1%, and the weight content of the N-methylpyrrolidone may be in the range of 84.85%±1%, based on the total weight of the black light absorbing composition.
[0083] In the present application, "black light absorbing composition" and "black light absorbing formulation" have the same meaning and can be used interchangeably.
[0084] In the black light-absorbing composition, PVDF plays a role in dispersing carbon black, and carbon black mainly plays a role in absorbing light. The weight contents of polyvinylidene fluoride, carbon black and N-methylpyrrolidone are within the above ranges, which can ensure that the black light-absorbing composition has a suitable viscosity range and a suitable absorbance.
[0085] In particular, since the black light-absorbing composition is particularly easy to absorb light, coating the black light-absorbing composition on the current collector can absorb laser energy to the maximum extent and transfer most of the absorbed laser energy to the current collector, which is beneficial to the cutting of the current collector; at the same time, coating the black light-absorbing composition on the pole piece can reduce the reflection of the current collector, which is beneficial to the concentration of heat on the current collector, thereby improving the efficiency of the current collector in absorbing laser energy and improving the efficiency of laser cutting.
[0086] In some embodiments, advantageously, the viscosity of the black light absorbing composition is in the range of 100 to 500 mPa·s, and can be optionally 300 to 500 mPa·s. The viscosity of the black light absorbing composition within the range can ensure a suitable coating thickness of the black light absorbing composition. If the viscosity is too high, the coating thickness may be too thin, and if the viscosity is too low, the coating thickness may be too thick.
[0087] In some embodiments, advantageously, the absorbance of the black light absorbing composition is ≥ 98.0%, optionally ≥ 99.9%.
[0088] The greater the absorbance of the black light-absorbing composition, the better. The greater the absorbance, the more laser energy can be absorbed and transferred to the current collector, which is helpful for cutting the current collector. If the value is too small, it may affect the speed of laser cutting the pole piece.
[0089] In some embodiments, the weight average molecular weight of the PVDF in the black light absorbing composition is in the range of 500,000 to 700,000. The weight average molecular weight of the PVDF in the black light absorbing composition is within the range, which can ensure that the black light absorbing composition has a suitable viscosity range and ensure the manufacturing efficiency of the black light absorbing composition, that is, ensure that the time required to produce the black light absorbing composition is less. If the molecular weight is too large or too small, it may result in an inappropriate viscosity range of the black light absorbing composition and low manufacturing efficiency.
[0090] In some embodiments, the average particle size of carbon black used in the black light absorbing composition is in the range of 0.1 to 1 μm. The average particle size of carbon black in the black light absorbing composition is within the above range, which can make the black light absorbing composition fine enough for gravure coating.
[0091] In the present application, the viscosity may be determined by conventional techniques in the art, and optionally, may be determined by a rotational viscometer.
[0092] In the present application, PVDF, quartz sand, carbon black, NMP, etc. can be obtained commercially or homemade. The weight average molecular weight of PVDF in the present application can be determined by conventional technical means in the art.
[0093] A third aspect of the present application provides a battery cell, comprising:
[0094] An electrode assembly, the electrode assembly comprising a main body and a current collector extending from at least one end of the main body;
[0095] The insulating glue described in the present application and / or the black light-absorbing composition described in the present application, wherein the insulating glue and / or the black light-absorbing composition covers at least a portion of the current collector; and
[0096] A shell in which the electrode assembly is accommodated.
[0097] A fourth aspect of the present application provides a battery, which includes the battery cell described in the present application.
[0098] A fifth aspect of the present application provides an electrical device, which includes the battery described in the present application, and the battery is used to provide electrical energy.
[0099] In this application, battery cells may include lithium-ion secondary batteries, lithium-ion primary batteries, lithium-sulfur batteries, sodium-lithium-ion batteries, sodium-ion batteries or magnesium-ion batteries, etc., and this application does not limit this. Battery cells may be cylindrical, flat, rectangular or other shapes, etc., and this application does not limit this. Battery cells are generally divided into three types according to the packaging method: cylindrical battery cells, square battery cells and soft-pack battery cells, and this application does not limit this.
[0100] The battery mentioned in the embodiments of the present application refers to a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery module or a battery pack. The battery generally includes a box for encapsulating one or more battery cells. The box can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells.
[0101] A battery cell includes an electrode assembly, an electrolyte and a shell. The electrode assembly includes a main body and a current collector extending from at least one end of the main body; the main body is composed of a positive electrode sheet, a negative electrode sheet and a separator. The battery cell mainly relies on the movement of metal ions between the positive electrode sheet and the negative electrode sheet to work. The positive electrode sheet includes a positive current collector and a positive active material layer. The positive active material layer is coated on the surface of the positive current collector. The positive current collector not coated with the positive active material layer protrudes from the positive current collector coated with the positive active material layer. The positive current collector not coated with the positive active material layer is die-cut to form a positive electrode ear. Taking lithium-ion batteries as an example, the material of the positive current collector can be aluminum, and the positive active material can be lithium cobalt oxide, lithium iron phosphate, ternary lithium or lithium manganese oxide, etc. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. The material of the isolation film may be PP (polypropylene) or PE (polyethylene), etc. In addition, the electrode assembly may be a winding structure or a stacked structure, and the embodiments of the present application are not limited thereto. In the present application, the insulating glue and / or the black light-absorbing composition covers at least a portion of the current collector extending from at least one end of the main body, that is, covers at least a portion of the current collector that is not coated with the active material layer.
[0102] Electrical equipment may be vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, electric tools, etc. Vehicles may be fuel vehicles, gas vehicles or new energy vehicles, and new energy vehicles may be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.; spacecraft include airplanes, rockets, space shuttles and spacecraft, etc.; electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc.; electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. This application does not impose any special restrictions on the above-mentioned electrical equipment.
[0103] The insulating glue described in the present application is at least located in the area of the current collector (i.e., the current collector extending from at least one end of the main body) close to the active material area, and has the following advantages: on the one hand, it is convenient to control the laser when die-cutting the current collector to avoid excessive energy affecting other areas; on the other hand, it can enhance the strength of the root of the current collector and play a role in insulation protection, avoiding the current collector or the pole ears formed after die-cutting or possible burrs from being inserted into the active material area or the main body, causing a short circuit.
[0104] The sixth aspect of the present application provides a method for cutting a current collector using laser, which includes using the above-mentioned insulating glue and / or the above-mentioned black light-absorbing composition.
[0105] As described above, the insulating adhesive described in the present application is used in the process of cutting the pole piece, which can improve the cutting rate and efficiency and avoid or reduce the generation of burrs during the cutting process. The black light-absorbing composition described in the present application can reduce the reflection of the aluminum foil to the laser and improve the absorption of the laser energy and transfer it to the current collector, thereby facilitating the cutting of the current collector. In the process of cutting the pole piece, the insulating adhesive described in the present application and the black light-absorbing composition described in the present application are used simultaneously, which can greatly improve the cutting speed while avoiding the generation of burrs and save laser energy.
[0106] It should be understood that although this application only mentions the method of using laser to cut the current collector, the insulating glue and black light-absorbing composition described in this application are suitable for application in any scenario or technical field that requires the use of laser or other forms of energy beams to cut metal or other materials.
[0107] It should be understood that the black light-absorbing composition described in the present application can be used alone, or can be used in combination with any insulating adhesive that is currently available or will appear in the future in the art to improve the current collector cutting efficiency.
[0108] In some embodiments, in the method of cutting the current collector using laser, the insulating glue described in the present application and the black light-absorbing composition described in the present application are used simultaneously, and the black light-absorbing composition is first coated on the current collector, and then the insulating glue is coated on the current collector coated with the black light-absorbing composition.
[0109] The simultaneous use of the light-transmissive insulating adhesive and the black light-absorbing composition described in this application can concentrate the laser energy on the cutting part of the pole piece to be cut to the greatest extent, significantly improving the cutting efficiency. In addition, the black light-absorbing composition described in this application is applied to the pole piece, which can quickly absorb the laser energy and transfer most of the energy to the current collector, thereby accelerating the cutting of the current collector. Therefore, the black light-absorbing composition described in this application is usually applied before the insulating adhesive is applied. For a cross-sectional schematic diagram and a top-down schematic diagram of the pole piece to be cut coated with both the insulating adhesive and the black light-absorbing composition, see Figure 1 and Figure 2 .
[0110] In some embodiments, in the method of cutting the current collector using laser, the black light-absorbing composition is coated on the cutting position on the current collector by gravure coating; optionally, the insulating glue is coated on the current collector to be cut by extrusion coating.
[0111] For the coating of the black light-absorbing composition, gravure coating can meet the requirement of 1 to 3 μm thickness of the black light-absorbing coating. It should be understood that any other coating method is also feasible, as long as it can achieve smooth coating of the black light-absorbing composition with appropriate thickness. For the coating of the insulating adhesive, extrusion coating can accurately control the coating thickness of the insulating adhesive. It should be understood that any other coating method is also feasible, as long as it can achieve smooth coating of the insulating adhesive with appropriate thickness.
[0112] The black light absorbing composition described in the present application is coated on the pole piece, which can quickly absorb laser energy and transfer most of the energy to the current collector, thereby accelerating the cutting of the current collector. Therefore, the black light absorbing composition described in the present application is usually coated on the cutting position of the pole piece irradiated by the laser. In actual operation, it is also possible to only coat the black light absorbing composition along a straight line (see Figure 6 ). The coating of the insulating glue described in the present application can improve the safety of the battery cell on the one hand, and can improve the efficiency of electrode cutting while avoiding or reducing the generation of burrs on the other hand. Therefore, it is usually coated on the edge of the active material on the electrode, and also on the current collector that is not in contact with the active material, see Figure 1 .
[0113] In some embodiments, in the method of cutting the current collector by laser, the insulating adhesive described in the present application is used, and the coating thickness of the insulating adhesive ranges from 10 to 60 μm, and the optional range is 30 to 40 μm. Optionally, the coating width is 2 to 5 mm, and the optional range is 3 to 4 mm.
[0114] Since the thickness of the insulating layer determines the size of the insulation resistance, the insulating glue coating thickness range within the above range can provide sufficient insulation performance. In addition, the insulating glue coating thickness range within the above range can also reduce or avoid the risk of short circuit caused by burrs formed during laser cutting of the positive electrode sheet piercing through the diaphragm and contacting the negative electrode or burrs formed during laser cutting of the negative electrode sheet piercing through the diaphragm and contacting the positive electrode (see Figure 7 The coating width of the insulating adhesive described in the present application is arbitrary and can be determined according to specific needs, common knowledge, or conventional technical means known to those skilled in the art.
[0115] In some embodiments, in the method of cutting the current collector using laser, the black light absorbing composition described in the present application is used, and the coating thickness of the black light absorbing composition is 1 to 5 μm, and optionally 1 to 3 μm. Optionally, the coating width is 0.5 to 2 mm, and optionally 0.5 to 1 mm.
[0116] The coating thickness and coating width of the black light-absorbing composition are within the above range, which can provide sufficient insulation performance and can reduce or avoid burrs during laser cutting, while increasing the cutting speed. In addition, it can also reduce or avoid the risk of short circuit caused by burrs formed during laser cutting of the positive electrode sheet, which penetrate the diaphragm and contact the negative electrode, or burrs formed during laser cutting of the negative electrode sheet, which penetrate the diaphragm and contact the positive electrode. It should be understood that the coating thickness and coating width of the black light-absorbing composition on the current collector are not limited to the above range, as long as it can cover part or all of the laser cutting area.
[0117] In some optional embodiments, when laser cutting is used to cut the pole piece, the laser cutting speed can be controlled at 90-130m / min, optionally 90-120m / min; when the laser cutting speed is controlled at 90-100m / min, the thickness of the insulating glue may need to be controlled at 40-60μm.
[0118] In addition, although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no conflict. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
[0119] Example
[0120] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0121] 1. Preparation of insulating glue
[0122] In each embodiment and comparative example in Table 1, the amount of NMP accounts for 100%-PVDF amount%-quartz sand amount%. The materials are added into a stirring tank with a dispersion disk according to the formula ratio in Table 1, and the materials are dispersed and stirred for 60 minutes to perform high-speed shearing, impact, crushing and dispersion on the materials, and the dispersion disk speed is 1200rpm. In each of the embodiments 1-4 and comparative examples 1-4, 650g of insulating glue is prepared.
[0123] 2. Preparation of black light-absorbing composition
[0124] In each embodiment and comparative example in Table 2, the amount of NMP accounts for 100%-PVDF amount%-carbon black amount%. The materials are added into a stirring tank with a dispersion disk according to the formula ratio in Table 2, and the materials are dispersed and stirred for 60 minutes to perform high-speed shearing, impact, crushing and dispersion on the materials, and the dispersion disk speed is 1200 rpm. In each of Examples 1-4 and Comparative Examples 1-4, 650 g of black light-absorbing composition are prepared.
[0125] 3. Performance parameter determination
[0126] (1) Viscosity measurement
[0127] The viscosity of the black light-absorbing composition and the insulating adhesive prepared in 1 and 2 was measured using a rotational viscometer.
[0128] (2) Determination of transparency and absorbance
[0129] The transparency of the insulating glue and the absorbance of the black light-absorbing composition were measured using an infrared spectrophotometer of model TJ-270-30A.
[0130] (3) Tear strength measurement
[0131] First, prepare a piece of insulating rubber sample with a length of 15cm, a width of 20mm, and a thickness of 50μm. Use a tensile machine to fix both ends of the sample, and then use a tensile speed of 50mm / min to stretch the sample until it breaks. Take the reading displayed by the tensile machine at the time of breakage and record it as the tear strength value.
[0132] The test results are shown in Table 1-2. The "%" in Table 1-2 refers to "% by weight".
[0133] 4. Coating of black light-absorbing composition and insulating glue and cutting of positive electrode sheets
[0134] (1) Source of positive electrode
[0135] The stirred positive electrode slurry is evenly coated on the aluminum foil by extrusion coating, then dried in an oven, and then rolled to obtain the positive electrode sheet.
[0136] (2) Coating
[0137] Examples 15-17: The insulating glue prepared in Example 5 is applied to the current collector by extrusion coating and is applied to the edge of the active material area (membrane area) (see the schematic diagram of the insulating glue position for details). Figure 1 ), the coating width is 4 mm, and the coating thickness is shown in Table 3. No black light absorbing composition is coated.
[0138] Examples 18-22: The black light-absorbing composition prepared in Example 6 was coated on the cutting line of the part to be cut in the positive electrode plate by gravure coating, with a coating width of 2 mm and a coating thickness as shown in Table 3. The insulating glue prepared in Example 5 was coated on the black light-absorbing composition by extrusion coating and on the edge of the active material area (membrane area) (see Figure 1 ), the coating width is 4 mm, and the coating thickness is shown in Table 3.
[0139] (3) Cutting
[0140] The cutting system mainly includes a laser cutting system, a dust removal device, a waste material discharging mechanism, and a joint detection and traction drive device. The pole piece is pulled by the traction device, and cutting is performed using a specific power and a specific cutting speed (see Table 3 for details). After cutting, the negative pressure provided by the dust removal device is used to vacuum the laser cutting area, and the removed waste is collected by the waste machine through the waste material discharging mechanism.
[0141] (4) Evaluation method of burrs after laser cutting:
[0142] The burrs on the cut positive electrode sheets in Examples 11-18 and Comparative Examples 9-11 were observed. The cut parts were observed with a microscope at 300 times magnification to check whether there were burrs. If there were burrs, the number of burrs was observed and recorded. The results are shown in Table 3.
[0143] Table 1: Formulation and properties of insulating adhesives
[0144]
[0145] It can be seen from Table 1 that compared with the insulating adhesive prepared using aluminum oxide in Comparative Examples 1-4, the insulating adhesive in Examples 1-5 has significantly higher transparency and more suitable viscosity and tear strength.
[0146] Table 2: Formulation and properties of black light absorbing compositions
[0147]
[0148] It can be seen from Table 2 that, compared with Examples 11-14, the black light-absorbing compositions in Examples 6-10 having appropriate weight and molecular weight of PVDF and weight ratio and particle size of carbon black can achieve better viscosity and absorbance.
[0149] Table 3: Laser cutting of positive electrode sheets
[0150]
[0151] Compared with Examples 15-17, Examples 18-22 use a black light-absorbing composition, so a smaller laser power can be used for cutting without generating burrs.
[0152] The thickness of the insulating glue applied in Comparative Example 5 is too small, only 10μm is applied, so 4 burrs are generated during the laser cutting process. Comparative Example 6 uses a laser cutting speed of 80m / min and produces 9 burrs; although Comparative Example 7 uses a thicker black light-absorbing composition, it uses a laser cutting speed of 90m / min and also produces 6 burrs. It can be seen that the laser cutting speed also has a certain influence on the generation of burrs, and the laser cutting speed should be controlled within a certain range during cutting. In Example 17, the laser cutting speed and laser power are the same as those in Comparative Example 7, but a thicker insulating glue is used, so no burrs are generated. In summary, consider controlling the laser cutting speed at 90-130m / min, and optionally 90-120m / min; when the laser cutting speed is controlled at 90-100m / min, the thickness of the insulating glue may need to be controlled at 40-60μm.
[0153] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A battery cell, characterized in that: include: An electrode assembly, the electrode assembly comprising a main body and a current collector extending from at least one end of the main body; An insulating glue comprising polyvinylidene fluoride, quartz sand and N-methylpyrrolidone and / or a black light-absorbing composition comprising polyvinylidene fluoride, carbon black and N-methylpyrrolidone, wherein the insulating glue and / or the black light-absorbing composition covers at least a portion of the current collector; and a housing in which the electrode assembly is housed, Wherein in the insulating glue, the weight content of the polyvinylidene fluoride is in the range of 3-7%, the weight content of the quartz sand is in the range of 13-23%, and the weight content of the N-methylpyrrolidone is in the range of 75-84%, based on the total weight of the insulating glue. The transparency of the insulating glue is ≥97%. The average particle size of the quartz sand used to prepare the insulating adhesive is in the range of 5 to 30 μm, and the weight average molecular weight of the polyvinylidene fluoride in the insulating adhesive is in the range of 600,000 to 700,000; In the black light-absorbing composition, the weight content of the polyvinylidene fluoride is in the range of 1 to 3%, the weight content of the carbon black is in the range of 5 to 35%, and the weight content of the N-methylpyrrolidone is in the range of 70 to 90%, based on the total weight of the black light-absorbing composition. The absorbance of the black light-absorbing composition is ≥ 98.0%, The average particle size of the carbon black used to prepare the black light-absorbing composition is 0.1-1 μm, and the weight average molecular weight of the polyvinylidene fluoride in the black light-absorbing composition is in the range of 500,000-700,000. 2 . The battery cell according to claim 1 , wherein the viscosity of the insulating glue is in the range of 500 to 2000 mPa·s. 3 . The battery cell according to claim 1 , wherein the tear strength of the insulating adhesive is in the range of 5 to 12 kN / m. 4 . The battery cell according to claim 1 , wherein the black light absorbing composition has a viscosity in the range of 100 to 500 mPa·s. 5 . The battery cell according to claim 1 , wherein the absorbance of the black light-absorbing composition is ≥ 99.9%.
6. A battery, characterized in that: The invention comprises the battery cell according to any one of claims 1 to 5.
7. An electrical equipment, characterized in that: Comprising a battery as claimed in claim 6, the battery is used to provide electrical energy.
8. A method for cutting a current collector using laser, comprising using the insulating glue and / or the black light-absorbing composition mentioned in any one of claims 1 to 7.
9. The method for cutting a current collector using laser according to claim 8, wherein the insulating glue and the black light-absorbing composition are used simultaneously, and the black light-absorbing composition is first coated on the current collector, and then the insulating glue is coated on the current collector coated with the black light-absorbing composition. 10 . The method for cutting a current collector using laser according to claim 8 or 9 , wherein the black light-absorbing composition is coated on the cutting position on the current collector by gravure coating. 11 . The method for cutting a current collector using laser according to claim 10 , wherein the insulating glue is coated on the current collector to be cut by extrusion coating. 12 . The method for cutting a current collector using laser according to claim 8 or 9 , wherein when the insulating adhesive is used, the coating thickness of the insulating adhesive is in the range of 10 to 60 μm. 13 . The method for cutting a current collector using laser according to claim 12 , wherein the coating thickness of the insulating glue is in the range of 30 to 40 μm. 14 . The method for cutting a current collector using laser according to claim 8 or 9 , wherein when the black light absorbing composition is used, the coating thickness of the black light absorbing composition is 1 to 5 μm. 15 . The method for cutting a current collector using laser according to claim 14 , wherein the coating thickness of the black light absorbing composition is 1 to 3 μm.
Citation Information
Patent Citations
Preparation method of absorbent for laser transmission welding of light-transmitting plastic
CN105968566A
Insulation glue spin-coating method for extruded coating machine of lithium ion battery
CN107994203A
Application of lithium ion battery during electrode assembly process
CN109755660A